An exploratory analysis of hazardous substances registered in the Mexican Pollutant Releases and Transfers Register in the State of Tamaulipas - Reyes-Anastacio, Hugo G.; Calderon, Jaqueline; Bautista-Vargas, Maria Esther; Gomez-Carpizo, Santiago (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
The North American Free Trade Agreement required Mexico, the United States and Canada to measure pollutants released and transferred to the environment. In Mexico, the Ministry of Environment and Natural Resources publishes an annual report of pollutants released or transferred by public and private facilities across industrial sectors. Each facility must report substances listed in Official Mexican Standard NOM-165-SEMARNAT-2013. In this study, we used the SINAT tool to obtain records of pollutant releases by municipalities in the state of Tamaulipas. We preprocessed and analysed the substances released in Tamaulipas and mapped them to their corresponding groups based on monographs from the International Agency for Research on Cancer (IARC). These groupings were then used to identify toxic substances—such as benzene, arsenic and asbestos—classified as carcinogenic to humans (Group 1) in Tamaulipas.